2010
DOI: 10.1590/s0101-31222010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Teste LERCAFÉ para sementes de cafeeiro com diferentes teores de água

Abstract: RESUMO -A determinação rápida do potencial germinativo é um fator importante a ser considerado no programa de produção de sementes. Nesse contexto, o teste LERCAFÉ tem se mostrado alternativa promissora, pois é um teste rápido e barato, além de ser de fácil execução e avaliação. Objetivou-se no presente trabalho definir novas combinações de concentração do hipoclorito de sódio, tempo de embebição e temperatura de exposição, para utilização do teste LERCAFÉ em sementes de cafeeiro com diferentes teores de água.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The results showed that increasing the immersion period, associated to the increase of the active chlorine concentration, cause excessive staining of the endosperm, precluding visual assessment by LERCAFE test. Zonta et al (2010) also failed to achieve satisfactory results for LERCAFE test when sodium hypochlorite solution with high levels of active chlorine combined with prolonged immersion periods was used. They reported that the test underestimated the results of coffee seeds germination under these conditions.…”
Section: Experiments 2: Adequacy Of the Lercafe Test Methodology With mentioning
confidence: 98%
See 2 more Smart Citations
“…The results showed that increasing the immersion period, associated to the increase of the active chlorine concentration, cause excessive staining of the endosperm, precluding visual assessment by LERCAFE test. Zonta et al (2010) also failed to achieve satisfactory results for LERCAFE test when sodium hypochlorite solution with high levels of active chlorine combined with prolonged immersion periods was used. They reported that the test underestimated the results of coffee seeds germination under these conditions.…”
Section: Experiments 2: Adequacy Of the Lercafe Test Methodology With mentioning
confidence: 98%
“…The coffee seeds immersed for 2 h in a sodium hypochlorite solution containing 2.5% of active chlorine, did not have greenish coloration in the endosperm, precluding their assessment (Table 2). Zonta et al (2010) when testing the efficiency of LERCAFE test, failed to achieve satisfactory results for the treatments in which the coffee seeds were immersed in a sodium hypochlorite solution containing 2.5% of active chlorine for the periods of 1 and 2 h, because there was absence of staining for these treatments. For treatments of 3.5% of active chlorine for 6 h, 5 and 6% of active chlorine for 2, 3 and 6 h, an intense dark green color was observed, occupying a large part of the seeds´ endosperm, this complicated their assessment by LERCAFE test, and data were not computed.…”
Section: Experiments 1: Adequacy Of the Lercafe Test Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed germination of seeds considerably extends the period of seedling formation process and may be attributed to properties of the seed cell walls and tissues, as well as to physical aspects such as endosperm hardness (Ferreira et al, 2018). The tissues surrounding the endosperm (micropylar endosperm) must be degraded (Zonta et al, 2010) so the radicle can then protrude and germination take place.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of time to germination test in the laboratories would be favorable for the production, commercialization, utilization and fiscalization of seeds (Guimarães et al, 2013). Tests such as the LERCAFE, which provides results in a relatively short period of time, are in the highest demand because they facilitate decision making at the different steps of the production process (Reis, Araújo, Dias, Sediyamam, & Meireles, 2010;Zonta, Araújo, Araújo, Reis, & Zonta, 2010).…”
Section: Introductionmentioning
confidence: 99%